The Impact of YouTube Viewing Intensity and Content Type on the Language Politeness of Early Childhood (A Study of 5-6-year-Old Children in Sirnabaya Village, Karawang) - Wahyuni, Sri; Rina Syafrida; Nur Rochimah (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2025)
This study aims to examine the influence of YouTube viewing intensity and content type on the language politeness of children aged 5–6 years in Sirnabaya Village, Karawang Regency. This research employed a quantitative approach with an Ex Post Facto design and involved 68 respondents selected through a simple random sampling technique. Data were collected using validated questionnaires covering three variables: YouTube viewing intensity (X1), type of YouTube content (X2), and language politeness (Y). Data analysis was conducted using multiple linear regression, supported by classical assumption tests including normality, linearity, multicollinearity, and heteroscedasticity. The results showed that variable X1 had a positive and significant effect on language politeness (Sig. = 0.007), while variable X2 had a negative and significant effect on language politeness (Sig. = 0.001). The regression equation obtained was Y = 88.075 + 0.357X1 – 0.348X2. The simultaneous test (F-test) indicated that both variables jointly had a significant effect on Y, with a significance value of 0.001 and an F-value of 12.116, which is greater than the F-table value of 3.138. The coefficient of determination (R² = 0.272) showed that 27.2% of the variation in language politeness could be explained by the intensity and type of YouTube content, while the remaining 72.8% was influenced by other factors such as parenting style, social environment, and other digital media. These findings highlight the importance of parental supervision regarding the duration and type of content children watch to ensure the resulting impact is positive. Early digital literacy education is also crucial in shaping polite language behavior in children.